2021
DOI: 10.3390/ijms222212410
|View full text |Cite
|
Sign up to set email alerts
|

D-Xylose Sensing in Saccharomyces cerevisiae: Insights from D-Glucose Signaling and Native D-Xylose Utilizers

Abstract: Extension of the substrate range is among one of the metabolic engineering goals for microorganisms used in biotechnological processes because it enables the use of a wide range of raw materials as substrates. One of the most prominent examples is the engineering of baker’s yeast Saccharomyces cerevisiae for the utilization of d-xylose, a five-carbon sugar found in high abundance in lignocellulosic biomass and a key substrate to achieve good process economy in chemical production from renewable and non-edible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 335 publications
(551 reference statements)
1
23
0
Order By: Relevance
“…It was shown that expression of a nuclear-localized Hxk2 activated xylose fermentation [ 25 ]. Effects of engineering the Snf3/Rgt2, SNF1/Mig1 and cAMP/PKA signalling pathways on xylose metabolism and fermentation in S. cerevisiae have been recently reviewed [ 26 ]. The role of xylose sensing/signalling in xylose metabolism and fermentation in the natural xylose-utilizing yeasts remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that expression of a nuclear-localized Hxk2 activated xylose fermentation [ 25 ]. Effects of engineering the Snf3/Rgt2, SNF1/Mig1 and cAMP/PKA signalling pathways on xylose metabolism and fermentation in S. cerevisiae have been recently reviewed [ 26 ]. The role of xylose sensing/signalling in xylose metabolism and fermentation in the natural xylose-utilizing yeasts remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…HXT1p induction at high d-glucose concentrations (20 g L −1 ) as well as repression at low-to-no d-glucose; full induction of SUC2p at low concentrations of d-glucose (1 g L −1 ), with repression at higher levels (> 5 g L −1 ) and only basal induction in carbon-free media; and TPS1p repression in response to preferred carbon sources such as d-glucose, d-fructose, and d-galactose (Fig. 7) [16]. Additionally, we observed the previously reported induction of SUC2p on d-xylose [18] as well as TPS1p induction, indicating both a carbon starvation response and a decrease in PKA activity, which further supports the [17]).…”
Section: Sugar Signaling Responses and Further Indications Of D-xylos...mentioning
confidence: 99%
“…Catabolite repression in S. cerevisiae is tightly regulated by the level of d-glucose and by the presence or absence of other naturally used carbon sources, such as d-galactose [15]. The absence of d-glucose, and the presence of certain sugars such as d-galactose or d-fructose, results in the expression of genes which enable the catabolism of these alternative sugars [16]. It remains unclear whether or not, and by extension how, d-xylose is sensed by S. cerevisiae.…”
Section: Introductionmentioning
confidence: 99%
“…However, its utilization of xylose naturally is lacking, requiring genetic engineering steps to insert one of the two xylose metabolism pathways to ethanol. Although yeast strains with these pathways are already used extensively, the challenge of xylose consumption remains, related to the cofactor imbalance on the oxidoreductive pathway, the need to further engineer or evolve exogenous xylose isomerases on the isomerase pathway, or inhibition of the xylose pathway by glucose due to sugar phosphorylation mechanisms [ 9 , 11 14 ].…”
Section: Introductionmentioning
confidence: 99%